1997
DOI: 10.1093/jn/127.3.458
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Lipid Intake During Pregnancy and Lactation Alters Milk Composition and Production and Litter Growth in Rats ,

Abstract: The relationship between dietary fat content and milk composition, production and litter growth was studied in rats fed during pregnancy and lactation purified diets of equal energy density containing 2.5 or 20 g fat/100 g diet. A subsample of rats (HL-EP group) fed the high lipid (HL) diet but pair-fed on an energy basis with the low lipid (LL) diet group was also studied in a separate experiment. Food intake, dam body weight and litter weight were recorded daily. Rats were milked on d 14 of lactation. Milk l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
70
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 24 publications
9
70
0
Order By: Relevance
“…However, there seems to be a similarity with the effects of a low-protein diet that also causes decreased birth weight and altered body mass (BM) development of the offspring during lactation (Fagundes et al, 2007;Desai et al, 1996and 1997. Excess of nutrients can lead to altered milk volume (King et al, 1993;Del Prado et al, 1997), lactose (Pine et al, 1994) as well as milk fat concentrations (Aoki et al, 1999;Tilton et al, 1999) subsequent to changes in mammary gland (MG) structure and gene expression (Flint et al, 2005;Rudolph et al, 2007). To our knowledge, the effects of a high dietary protein intake during gestation and lactation on murine MG histology and mRNA abundance have not been determined before.…”
Section: Introductionmentioning
confidence: 99%
“…However, there seems to be a similarity with the effects of a low-protein diet that also causes decreased birth weight and altered body mass (BM) development of the offspring during lactation (Fagundes et al, 2007;Desai et al, 1996and 1997. Excess of nutrients can lead to altered milk volume (King et al, 1993;Del Prado et al, 1997), lactose (Pine et al, 1994) as well as milk fat concentrations (Aoki et al, 1999;Tilton et al, 1999) subsequent to changes in mammary gland (MG) structure and gene expression (Flint et al, 2005;Rudolph et al, 2007). To our knowledge, the effects of a high dietary protein intake during gestation and lactation on murine MG histology and mRNA abundance have not been determined before.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, milk availability has a direct impact on pup growth 26,32 . Pups from dams fed a high-fat diet (20%) with adequate protein content are significantly heavier than controls on the sixth day of life, and the difference in weight is even greater by day nine 32 . These dams not only produced more milk, but their milk also presented higher fat, protein and energy contents.…”
Section: Discussionmentioning
confidence: 99%
“…Also, low dietary protein increases the fat content of milk from the fourth day of lactation 6 . High-fat diets increase the fat content and energy density of the milk, causing greater satiety and, therefore, less intake 32 . These facts may explain to a certain degree the smaller skull growth seen in the POFG pups, but the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…In trying to understand these effects and living beings' capability to adapt to different forms of aggression, many researchers have been investigating the effects of different kinds of nutritional injury to the nervous system in the early phases of its development. These studies have shown morphologic, neurochemical, endocrine and functional alterations (Morgane et al 1993;Del-Prado et al, 1997).…”
Section: Introductionmentioning
confidence: 98%